Assessment of Vehicle Maintenance Culture and Its CostEffectiveness: The Case of the University for Development Studies - Seniwoliba , A. J.; Awuni, A. M. (European Scientific Journal, ESJ, 2023)
The University for Development Studies is a public university in Ghana that owns and manages a fleet of vehicles. The university, however, faces numerous challenges in terms of maintaining its fleet of vehicles. Reports from the various campuses of the university indicate that most of the vehicles that broke down were at various mechanic shops and needed urgent attention. In order to propose solutions to the university’s problems, the study sought to discover the causes of the university’s vehicles’ frequent breakdowns, why most of the vehicles were left unattended at the various mechanic shops, and why the cost of vehicle maintenance was so high. The study population comprised 55 vehicles and 30 drivers who use the vehicles in the various offices, directorates, and the pool (general usage) at the Central Administration. However, data on 34 vehicles were available for the study, which was far more than the needed representation. Ten drivers were sampled to participate in the study using a simple random sampling approach. Face-to-face interviews and one-on-one correspondence were conducted with the selected sample (drivers). The researchers used open-ended questions to gather relevant data from the respondents. The secondary data was obtained from mechanics and technicians who presented their bills for payment at the Transport Office of the University. Both qualitative and quantitative methods were used in analyzing the data collected. The data were analyzed using grounded theory and Excel sheets. The study revealed issues such as frequent vehicle breakdowns that went unattended at mechanic shops and high maintenance costs as a result of a poor maintenance culture, insufficient funding, delays in the release of funds for maintenance, inflation of the cost of spare parts, the use of substandard materials, the age of the vehicle, and the insufficient knowledge and skills of mechanics and technicians. It is therefore recommended that a formalized maintenance department be established within the university and sufficiently equipped with tools and spare parts. The department should be staffed with well-qualified and experienced mechanics with the requisite practical knowledge and skills in vehicle maintenance. This will allow fast and quick responses to vehicle maintenance issues.